The influence of sub-toxic dose xenobiotic on immune response of experimental animals = Вплив субтоксичних доз ксенобіотиків на імунну відповідь у експериментальних тварин = Влияние субтоксических доз ксенобиотиков на иммунный ответ у экспериментальных животных - Bagmut, I. Yu.; Popova, T. M.; Titkova, A. V.; Philipchenko, S. M.; Shepylieva, N. V. (Journal of Education, Health and Sport, 2017)
Bagmut I. Yu., Popova T. M., Titkova A. V., Philipchenko S. M., Shepylieva N. V. The influence of sub-toxic dose xenobiotic on immune response of experimental animals = Вплив субтоксичних доз ксенобіотиків на імунну відповідь у експериментальних тварин = Влияние субтоксических доз ксенобиотиков на иммунный ответ у экспериментальных животных. Journal of Education, Health and Sport. 2016;6(11):629-639. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.200862 http://ojs.ukw.edu.pl/index.php/johs/article/view/4066 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 30.11.2016. UDK 613.6.027: 663.97.05 THE INFLUENCE OF SUB-TOXIC DOSE XENOBIOTIC ON IMMUNE RESPONSE OF EXPERIMENTAL ANIMALS I. Yu. Bagmut, T. M. Popova, A. V. Titkova, S. M. Philipchenko, N. V. Shepylieva Kharkiv Medical Academy of Postgraduate Education Summary The polyester is widely used in all sectors of the economy. The polyester influence on the cellular and humoral immunity has been required an integrated research. The actual medical-biological problem is immune deficiency indicators and they need to substantiate during immune toxicological research. One of the scientific directions is the investigation of polyols influence on immunobiological resistance of the human organism. The results can be used for developing of methods to increase the non-specific reactivity. This study examines mechanisms of cellular and humoral immunity disorders of mice and rats after prolonged oral administration of Laprol- 604. Oral consumption of Laprol-604 has been shown to result in inhibition of cellular and humoral immunity of laboratory animals. The study has been performed as part of the research topic of Kharkiv Medical Academy of Postgraduate Education «Cellular-molecular mechanisms of inflammation associated with chronic diseases», the state registration number 015U001186. Keywords: polyester, Laprol-604, humoral immunity, cellular immunity, spleen, lymph nodes. ВПЛИВ СУБТОКСИЧНИХ ДОЗ КСЕНОБІОТИКІВ НА ІМУННУ ВІДПОВІДЬ У ЕКСПЕРИМЕНТАЛЬНИХ ТВАРИН І. Ю. Багмут, Т. М. Попова, А. В. Тіткова, С. М. Філіпченко, Н. В. Шепілева Харківська медична академія післядипломної освіти Резюме Поліестер широко використовується у всіх секторах економіки. Вплив поліестеру на вираженість клітинного та гуморального імунітет вимагає комплексного дослідження. Важливою медико-біологічною проблемою є показники імунодефіциту, що і було вивчено при імунних токсикологічних дослідженнях. Одним з наукових напрямків є вивчення впливу поліолів на імунобіологічну резистентність організму людини. Отримані результати можуть бути використані для розробки методів підвищення неспецифічної реактивності. У даній роботі розглядаються механізми порушень клітинного і гуморального імунітету у мишей і щурів після тривалого перорального введення Лапрола-604. Показано, що пероральне введення Лапрола-604 призводить до пригнічення клітинного і гуморального імунітету у тварин. Дослідження було проведено в рамках науково-дослідної теми Харківської медичної академії післядипломної освіти «Клітинно-молекулярні механізми запалення, пов'язані з хронічними захворюваннями» (номер державної реєстрації 015U001186). Ключові слова: поліестер, Лапрол-604, гуморальний імунітет, клітинний імунітет, селезінка, лімфатичні вузли. ВЛИЯНИЕ СУБТОКСИЧЕСКИХ ДОЗ КСЕНОБИОТИКОВ НА ИММУННЫЙ ОТВЕТ У ЭКСПЕРИМЕНТАЛЬНЫХ ЖИВОТНЫХ И. Ю. Багмут, Т. М. Попова, А. В. Титкова, С. М. Филипченко, Н. В. Шепилева Харьковская медицинская академия последипломного образования Резюме Полиэстер широко используется во всех секторах экономики. Влияние полиэстера на выраженность клеточного и гуморального иммунитет требует комплексного исследования. Важной медико-биологической проблемой являются показатели иммунодефицита, что и было изучено при иммунных токсикологических исследованиях. Одним из научных направлений является изучение влияния полиолов на иммунобиологическую резистентность организма человека. Полученные результаты могут быть использованы для разработки методов повышения неспецифической реактивности. В настоящей работе рассматриваются механизмы нарушений клеточного и гуморального иммунитета у мышей и крыс после длительного перорального введения Лапрола-604. Показано, что пероральное введение Лапрола-604 приводит к угнетению клеточного и гуморального иммунитета у животных. Исследование было проведено в рамках научно-исследовательской темы Харьковской медицинской академии последипломного образования «Клеточно-молекулярные механизмы воспаления, связанные с хроническими заболеваниями» (номер государственной регистрации 015U001186). Ключевые слова: полиэстер, Лапрол-604, гуморальный иммунитет, клеточный иммунитет, селезёнка, лимфатические узлы.